KAJIAN POTENSI DAN STRATEGI PENGEMBANGAN EKOWISATA DI HUTAN MERANTI KABUPATEN KOTABARU-KALIMANTAN SELATAN - Ifnu Al Amin; Tatag Muttaqin; Erni Mukti Rahayu (Universitas Muhammadiyah Malang, 2018)
This study aims to examine the potential of natural attractions as a tourist attraction and ecotourism development strategy in meranti forest in order to give influence to the ecological, eco and social development of the community on ecotourism management in meranti forest. This research was conducted in Meranti Kotabaru Forest, South Kalimantan in January-February 2017. The basic method used in this research is to assess the potential of attraction, the condition of the area, the condition of the people and the tourists and the management of the area. Data analysis was done by descriptive method.The results showed that the Ecotourism Area of Meranti Forest has potential that can still be developed, All people strongly support the empowerment of society because it can improve the living standard of the surrounding community. Results of SWOT Analysis can be used as a development strategy of Meranti Forest Ecotourism, namely; a) Strengthening ecotourism concept for Ecotourism of Meranti Forest, b) Reorganization of space for ecotourism activities, c) Encouraging linkage with travel unit, d) Encouraging participation and empowerment of tourism community, e) Encouraging strategic business units, f) Conduct a vigorous promotion.